A non-aristonectine plesiosaur from Antarctica reveals new data on the mandibular symphysis of elasmosaurids - O'gorman, Jose Patricio; Bona, Paula; de Los Reyes, Leonardo Martín; Raffi, María Eugenia; Reguero, Marcelo Alfredo (Alcheringa: An Australasian Journal of Palaeontology)
Elasmosaurids are one of the most abundant fossil marine reptile groups identified from the Upper Cretaceous strata of Antarctica. However, the documented record of intact elasmosaurid skull remains is scarce. In this study, we describe the first non-aristonectine elasmosaurid skeleton from Antarctica that preserves an associated lower jaw. This specimen displays a unique character state combination including three symphyseal alveoli, the angle between the mandibular rami exceeding 90 , and the absence of a ventral symphyseal sulcus or keel. This mandibular configuration has not been observed previously among elasmosaurids, prompting comparisons with other described examples and suggesting that mandibular morphology reached a variability peak during the Maastrichtian, which might be reflective of increased trophic diversity. Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Bona, Paula. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: de Los Reyes, Leonardo Martín. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Raffi, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de ...